Who invented television? Philo Farnsworth - Carson, Mary Kay. (Berkeley Heights, NJ : Enslow Elementary, 2012)
"Learn about Philo Farnsworth, and see how he invented tv"--Provided by publisher.
Includes bibliographical references (p. 22-23) and index.
2.9
K-3
K-3
Keywords: Farnsworth, Philo Taylor, -- 1906-1971 -- Juvenile literature; Farnsworth, Philo Taylor, -- 1906-1971.; Farnsworth, Philo Taylor, -- 1906-1971.; Electrical engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Television -- History -- Juvenile literature; Electrical engineers; Inventors; Television -- History; Electrical engineers -- Biography; Inventors -- United States -- Biography; Television -- History